Pengaruh Kepuasan Nasabah Terhadap Menggunakan Mobile Banking (M-Banking) Pada Bank BCA Cabang Banda Aceh - Syamsul Rizal; Munawir Munawir (Jurnal EMT KITA, 2017)
The purpose of this study is to determine the effect of service quality to consumer decisions using M-Banking at Bank BCA Branch Banda Aceh. This research was conducted at Bank BCA Branch of Banda Aceh to M-Banking consumer, and the object of research is about consumer's satisfaction in using M-Banking. Sampling was done by "Convinience Sampling" method to 100 consumers using M-Banking at Bank BCA Branch of Banda Aceh. From the result of the research, it can be seen that customer satisfaction level toward M-Banking user at Bank BCA Branch of Banda Aceh is seen from variable of reliability, keresponsifan, belief, empathy and tangible is satisfying this can be seen from the acquisition of the average value of the responses of respondents to all variable is above 3,500. The results showed that the determinant coefficient (R2) was 92.2 percent indicating that the variables of reliability, responsiveness, confidence, empathy and tangible variables influence the level of customer satisfaction using M-Banking at BCA Bank of Banda Aceh Branch at 92.2 percent and the rest 7.8 percent is influenced by other variables outside of this research model. Testing done either by using F-test or by using t-test, it can be concluded that all independent variables in this study significantly influence both partially and simultaneously to customer satisfaction using M-Banking at Bank BCA Branch Banda Aceh, in other words the hypothesis in this study is accepted. To cultivate a sense of trust to consumers, recommended features, speed and other services as well as security in the use of M-Banking should be increased so that consumer confidence increases.